South Korea’s 70-Year Endeavor for Foreign Policy, National Defense, and Unification - Nam, Sung-Wook. author. aut Link
XV, 291 p.
Keywords: licy minds together in contemplating the risks and rewards of finally ending the 70 year stalemate between North and South Korea through reunification. While North Korea is in conflict with the United States over denuclearization and regime security, the South Korean government is focusing on economic development preparing for the day when the two Koreas are unified. This book will help scholars, activists and policy-makers from all over the world systematically understand the current diplomatic and security issues in the Korean peninsula. Sung-Wook Nam is Professor at the Department of Unification and Diplomacy, Korea University, South Korea. Sang-Woo Rhee was Professor of Political Science at Sogang University, South Korea, and served as President of Hallym University, South Korea. Myongsob Kim is Professor at the Department of Political Science and Diplomacy, Yonsei University, South Korea. Young-Ho Kim is Professor at the Department of Political Science and Foreign Affairs, Sungshin Women’s University, South Korea. Yong-Sub Han is Professor at the Graduate School of Security at the Korea National Defense University, South Korea. Young-Soon Chung is Professor at the Graduate School of Korean Studies, Academy of Korean Studies, South Korea. Sung-Ok Yoo was a member of South Korean National Security Council and served as President of the Institute for National Security Strategy in South Korea.